Conformational changes and the formation of new bonds achieving robust nanoemulsions by electrostatic interactions between whey protein isolate and chondroitin sulfate. (March 2023) - Wang, Yuxiao; Li, Mo; Wen, Xin; Tao, Haiteng; Wang, Kunli; Fu, Rao; Tao, Hongxun; Wang, Fuying; Chen, Nan; Ni, Yuanying
Abstract: Nanoemulsions are a promising approach for the targeted delivery and precise release of bioactive ingredients in food or pharmaceuticals. Nevertheless, there are some limitations for certain applications because they are susceptible to break down through physical instability mechanisms. In this study, we explored an effective, rapid, and green strategy to engineer robust nanoemulsions with the electrostatic complexes of whey protein isolate (WPI) and chondroitin sulfate (CS) induced by ultrasonication and acidic conditions. At an optimized CS:WPI ratio of 4:6, the nanoemulsions exhibited a desirable average particle size of 241.5 ± 2.2 nm and a highest shell thickness ratio of 37.26%. Our findings revealed that CS could bind with WPI using ultrasonication under neutral conditions, whereas the robust nanoemulsions only formed under acidic conditions. The robust nanoemulsions exhibited a higher crystallinity at 2 θ = 19.6° and a higher content of β-sheet. Polarity amino acids were essential in forming new bonds, including Thr, Lys, His, Gly, Glu, and Asp. Our study revealed conformational changes and the formation of new bonds achieving considerably robust nanoemulsions and provided a green and sustainable method for efficiently encapsulating lipid-soluble hydrophobic ingredients. Graphical abstract: Image 1 Highlights: Conformational changes and the formation of new bonds achieved robust nanoemulsions. Polarity amino acids were essential in forming new bonds. Engineering robust nanoemulsions from perspectives of crystal and secondary structures.